Estimating permeability from field measurements of seismic attenuation in fractured chalk - Payne, S; Worthington, M; Odling, N; West, L (2007)
Broadband (100-4000 Hz) cross-hole seismic data have been acquired at a borehole test site where extensive hydrological investigations have previously been performed, including in situ estimates of permeability. The rock type is homogeneous chalk and fractures and bedding planes have been identified from well logs. High values of seismic attenuation, Q = 22 ≤ 27 ≤ 33, were observed over a 10 m depth interval where fracture permeability values of 20-50 darcy had been recorded. An attempt has been made to separate the attenuation due to scattering and intrinsic mechanisms. The estimated values of intrinsic attenuation, Q = 31 ≤ 43 ≤ 71, have been reproduced using a number of current theories of seismic-wave propagation and fluid-flow-induced seismic attenuation in cracked and fractured media. A model that considers wavelength-scale pressure gradients is the preferred attenuation mechanism. Model parameters were obtained from the hydro-geological and seismic data. However, we conclude that it is not possible to use seismic Q to measure rock permeability remotely, principally because of the inherent uncertainties arising from model parameterisations. © 2007 European Association of Geoscientists and Engineers.